Effectiveness of yoga and naturopathy intervention on palmar psoriasis - A case report - Akila,; Narayanasamy, Mangaiarkarasi; Chidambaram, Yogapriya; Boopalan, Deenadayalan; Poornachandran, Prabu (Indian Journal of Integrative Medicine, 2022)
Palmar psoriasis is a chronic variant of psoriasis that affects the skin of the palms producing significant functional disability. It is usually triggered by environmental factors such as trauma, infections, medicines, metabolic / hormonal factors, stress, alcohol use, smoking and lifestyle. Worldwide 2% population are affected by psoriasis, whereas in India 0.4% - 2.8% are affected. Yoga and Naturopathy (YN) is a widely used traditional healing science that encompasses holistic approach in prevention and treatment of diseases. A 25 years old male presented with palmar psoriasis underwent YN- based lifestyle interventions which includes hydrotherapy, mud therapy, yoga therapy and acupuncture for a period of 24 days. Baseline PASI score and PSS scores were 1.26% and 26 respectively. Both PASI score and PSS score reduced considerably after treatment. This case report indicates that YN have a positive role in reinstating palmar psoriasis. However large-scale studies are warranted to bestow better care.